Heat storage stable polyamide wax micro powder

By using diamines with linear symmetric structure and modified nanotitanium dioxide in polyamide wax micropowder, the thermal stability and dispersion are improved, and the problem of degradation of rheological properties of polyamide wax rheological agents after thermal storage is solved. , significantly improves the anti-sag performance and the service life of the coating.

CN119264720AInactive Publication Date: 2025-01-07ZHEJIANG FENGHONG NEW MATERIAL

Patent Information

Application Number
CN202411784464.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The rheological performance of existing polyamide wax rheological agents decreases after heat storage, and the anti-sag performance becomes worse, resulting in a reduced coating performance.

Method used

By introducing diamines with linear symmetric structures and modified nanotitanium dioxide into polyamide wax micropowder, the integrity and crystallinity of its crystal structure are improved, and the surface modification of nanotitanium dioxide is used to enhance the nucleation effect by using long-chain fatty acids to enhance the nucleation effect. and dispersibility.

Benefits of technology

It significantly improves the heat storage and sag resistance of polyamide wax rheogenic agents, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer chemistry, and particularly relates to heat storage stable polyamide wax micro powder. The polyamide wax comprises polyamide wax micro-powder, preparation raw materials of the polyamide wax micro-powder comprise combined organic amine, and the combined organic amine comprises m-xylylenediamine and diamine with a linear symmetric structure; the modified nano titanium dioxide is obtained by carrying out surface modification on nano titanium dioxide through long-chain fatty acid. The modified nano titanium dioxide is added in the preparation process of the polyamide wax rheological agent, so that the thermal storage resistance of the polyamide wax rheological agent can be improved, and the anti-sagging performance of the polyamide wax rheological agent can be improved; according to the polyamide wax rheological agent, diamine with a linear symmetrical structure is used for replacing part of m-xylylenediamine, so that the thermal storage resistance of the polyamide wax rheological agent can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating additives, and in particular relates to a heat storage stable polyamide wax micropowder. Background Art

[0002] Polyamide wax rheological agents are a type of thixotropic additives, commonly used in coatings, inks, adhesives, lubricants and other fields. Polyamide wax rheological agents have strong thixotropy and only need to be added in small amounts to provide excellent rheological properties. Low-temperature activated wax powder is one of the forms of polyamide wax products, and its active ingredient content is 100%. This type of wax powder that can be directly added is cost-effective and more conducive to current environmental protection policies. However, during use, some defects are also exposed. For example, after a period of hot storage (one or two months), the coating using low-temperature activated wax powder usually shows a decrease in rheological properties and deterioration in anti-sagging performance, which greatly reduces the performance of the coating.

[0003] In summary, there is a need for a polyamide wax rheological agent that is more resistant to heat storage. Summary of the invention

[0004] The invention aims to provide a heat storage stable polyamide wax micropowder.

[0005] The technical solution adopted by the present invention to solve the above problem is: a heat storage stable polyamide wax micropowder, comprising the following components by weight: 100-150 parts of polyamide wax powder, wherein the raw materials for preparing the polyamide wax powder include a combination of organic amines, and the combination of organic amines includes meta-xylylenediamine and a diamine with a linear symmetrical structure; 5-10 parts of modified nano titanium dioxide, wherein the modified nano titanium dioxide is obtained by surface-modifying the nano titanium dioxide with a long-chain fatty acid.

[0006] Among them, in "polyamide wax micropowder", "wax" usually refers to a substance with waxy properties, rather than natural wax or paraffin itself. "Micropowder" usually means that the polyamide wax particle size is at the micron level.

[0007] The reason for the decline in the rheological properties of polyamide wax rheological agents after heat storage and the deterioration of the anti-sagging performance is that the crystal structure in the wax powder is imperfect. During the long-term heat storage process, these imperfect crystals are slowly dissolved by the solvent in the coating, resulting in the failure of some hydrogen bonds and the destruction of the three-dimensional structure built by the wax powder in the coating system. Macroscopically, this is manifested as a significant reduction in the thickening and rheological effects of the wax powder. From a microscopic structure perspective, the polyamide wax in the prior art is usually formed based on m-xylenediamine. For example, a high-solids waterborne polyamide wax disclosed in the Chinese invention patent with the publication number CN114163864B has a molecular structure that is not a linear structure but is similar to a "zhi" character structure, where the "mouth" represents a benzene ring and the "eight" represents two organic acid chains. Obviously, when the molecular chains of this structure are closely arranged, due to the steric hindrance effect of the benzene ring, it is difficult to form a very dense crystal structure. During the long-term contact with solvent molecules, the solvent molecules can easily penetrate into the unit cell through the loose part of the crystal, that is, the position of the benzene ring, which greatly promotes the dissolution of the microcrystals.

[0008] Based on this, in order to improve the integrity of its crystal structure, during the synthesis of the wax powder, some linear symmetric binary organic amines are introduced. These linear symmetric diamines finally result in linear polyamide molecules. After synthesis, an appropriate cooling process is adopted to enable the linear polyamide molecules to form dense crystal nuclei and enhance the thermal stability of the microcrystals.

[0009] In addition, in order to further improve the integrity of its crystal structure, nano-titanium dioxide is introduced as a nucleating agent, which can promote the crystallization of the wax powder, increase the crystallinity and crystallization rate, enhance the thermal stability and mechanical properties of the wax powder, and improve the dispersibility and stability of the wax powder in the coating system.

[0010] Particularly, in this application, the nano-titanium dioxide is also modified by surface treatment with long-chain fatty acids, which further improves the compatibility between the nano-titanium dioxide and the polyamide wax, reduces the surface energy, enhances the nucleation effect, thereby reducing agglomeration and improving the dispersion stability.

[0011] A further preferred technical solution is that: the long-chain fatty acid includes one of lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, and lignoceric acid.

[0012] Among them, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, and lignoceric acid are all saturated long-chain fatty acids. There are no double bonds in saturated fatty acid molecules, so they are more stable and not prone to oxidation or other chemical reactions. Due to the stability of their structure, saturated fatty acids are more heat-resistant. In particular, shorter chain lengths may provide limited hydrophobicity, but better dispersibility, while longer chain lengths have extremely high hydrophobicity, but may reduce dispersibility. Stearic acid provides both good hydrophobicity and balanced dispersibility, and is suitable for use in the modification of nano-silica.

[0013] A further preferred technical solution is that the long-chain fatty acid includes one of oleic acid, linoleic acid, linolenic acid, and arachidonic acid.

[0014] A further preferred technical solution is that the nano titanium dioxide includes one of rutile, anatase, brookite and mixed crystal forms.

[0015] Among them, the anatase type is usually easier to surface-modify with organic molecules, including long-chain fatty acids, due to its higher surface activity. Surface modification can improve its dispersibility and stability in organic media.

[0016] A method for preparing a heat storage stable polyamide wax micropowder according to any one of the above items comprises the following steps: S01. A measured amount of an acid is added to the reaction device and the temperature is raised to 100-140°C until the acid is completely melted into a liquid to obtain a product 1; S02. Slowly add the combined organic amine to the product one, the molar ratio of the first type of acid to the organic amine is 2:1, and after the addition is completed, the temperature is raised to 150-160° C. and reacted for a period of time until the acid value drops below 5 to obtain product two; S03. Adding a second type of acid to the product two, the molar ratio of the first type of acid to the second type of acid is (0.85-0.95): (0.05-0.15), and continuing the reaction at a constant temperature until the acid value is less than 5 to obtain a product three; S04. Add the modified nano titanium dioxide to the product three and stir to mix. After mixing, the material can be discharged. After the wax block is completely cooled, it is crushed, coarsely crushed and air flow milled until the particle size of the powder is D98≤15μm, so as to obtain the polyamide wax powder.

[0017] Among them, one type of acid is hydroxyl-containing acid, such as 10-hydroxydecanoic acid, 12-hydroxylauric acid, 12-hydroxystearic acid, ricinoleic acid, etc.; the second type of acid is common fatty acids, such as caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, hexadecanoic acid, and stearic acid.

[0018] D98≤15μm means that among all the particles, 98% of the particles have a particle size less than or equal to 15μm.

[0019] A further preferred technical solution is that in step S02, the organic amines in the combination include meta-xylylenediamine and diamines with a linear symmetrical structure, wherein meta-xylylenediamine accounts for 80%-95% of the total amount of the organic amines in the combination, and the diamines with a linear symmetrical structure account for 5%-20% of the total amount of the organic amines in the combination.

[0020] A further preferred technical solution is that the diamine with a linear symmetrical structure includes a mixture of one or more of ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,10-decanediamine, p-phenylenediamine, and 4,4'-diaminodicyclohexylmethane.

[0021] The method for preparing the modified nano titanium dioxide according to any one of the above items comprises the following steps: S11. Add an appropriate amount of nano-titanium dioxide powder to the solvent and treat with ultrasound for 20-30 min to obtain a dispersed nanoparticle solution; S12. Dissolving a long-chain fatty acid in ethanol, wherein the mass of the long-chain fatty acid is 1-5% of the mass of the nano-titanium dioxide, to obtain a fatty acid solution; S13. The dispersed nanoparticle solution was transferred to a three-necked flask, and the fatty acid solution was slowly added dropwise, the reaction temperature was controlled between 60-80° C., and the reaction was stirred for 2-4 h to obtain a modified nano-titanium dioxide suspension; S14. Cool the modified nano-titanium dioxide suspension to room temperature, collect the modified nano-titanium dioxide by centrifugation or filtration, repeatedly wash the product with ethanol or deionized water to remove unreacted stearic acid, and vacuum dry the washed product at 60-80°C for 12-24h, then lightly grind the dried product, and sieve it through a sieve to obtain the modified nano-titanium dioxide.

[0022] A further preferred technical solution is that in step S11, the ultrasonic treatment power is 400-500W.

[0023] A further preferred technical solution is that in step S11, the solvent is anhydrous ethanol or isopropanol, and the mass ratio of the nano titanium dioxide powder to the solvent is 1: (10-100).

[0024] In summary, the present invention has the following benefits: 1. The present invention adds modified nano titanium dioxide during the preparation process of the polyamide wax rheological agent, which can improve the heat storage resistance and anti-sagging performance of the polyamide wax rheological agent; 2. The present invention uses a diamine with a linear symmetrical structure to replace part of the m-xylylenediamine, which can greatly improve the heat storage resistance of the polyamide wax rheological agent; 3. The modified nano titanium dioxide added in the present invention uses anatase nano titanium dioxide and is modified with stearic acid, which has a more significant effect on improving the heat storage resistance of the polyamide wax rheological agent. DETAILED DESCRIPTION

[0025] The present invention is described in further detail below.

[0026] Example 1 In this embodiment, the method for preparing the polyamide wax powder comprises the following steps: S01. A measured amount of an acid is added to the reaction device and the temperature is raised to 100°C until the acid is completely melted into a liquid to obtain a product 1; S02. Slowly add the combined organic amine to the product one, wherein the molar ratio of the first type of acid to the organic amine is 2:1, and after the addition is completed, the temperature is raised to 150° C. and reacted for a period of time until the acid value drops below 5 to obtain product two; S03. Adding a second type of acid to the product two, wherein the molar ratio of the first type of acid to the second type of acid is 0.85:0.05, and continuing the reaction at a constant temperature until the acid value is less than 5 to obtain a product three; S04. Add the modified nano titanium dioxide to the product three and stir to mix. After mixing, the material can be discharged. After the wax block is completely cooled, it is crushed, coarsely crushed and air flow milled until the particle size of the powder is D98≤15μm, so as to obtain the polyamide wax powder.

[0027] Example 2 In this embodiment, the method for preparing the polyamide wax powder comprises the following steps: S01. A measured amount of an acid is added to the reaction device, and the temperature is raised to 140°C until the acid is completely melted into a liquid to obtain a product 1; S02. Slowly add the combined organic amine to the product one, wherein the molar ratio of the first type of acid to the organic amine is 2:1, and after the addition is completed, heat to 160° C. and react for a period of time until the acid value drops below 5 to obtain product two; S03. Adding a second type of acid to the product two, wherein the molar ratio of the first type of acid to the second type of acid is 0.95:0.15, and continuing the reaction at a constant temperature until the acid value is less than 5 to obtain a product three; S04. Add the modified nano titanium dioxide to the product three and stir to mix. After mixing, the material can be discharged. After the wax block is completely cooled, it is crushed, coarsely crushed and air flow milled until the particle size of the powder is D98≤15μm, so as to obtain the polyamide wax powder.

[0028] Example 3 In this embodiment, the preparation method of the modified nano titanium dioxide comprises the following steps: S11. Add an appropriate amount of nano-titanium dioxide powder to the solvent and treat with ultrasound for 20 min to obtain a dispersed nanoparticle solution; S12. Dissolving a long-chain fatty acid in ethanol, wherein the mass of the long-chain fatty acid is 1% of the mass of the nano-titanium dioxide, to obtain a fatty acid solution; S13. The dispersed nanoparticle solution was transferred to a three-necked flask, and the fatty acid solution was slowly added dropwise, the reaction temperature was controlled at 60° C., and the reaction was stirred for 2 h to obtain a modified nano-titanium dioxide suspension; S14. The modified nano-titanium dioxide suspension is cooled to room temperature, and the modified nano-titanium dioxide is collected by centrifugation, and the product is repeatedly washed with ethanol to remove unreacted stearic acid, and the washed product is vacuum dried at 60°C for 12 hours, and then the dried product is lightly ground and sieved through a sieve to obtain the modified nano-titanium dioxide.

[0029] Example 4 In this embodiment, the preparation method of the modified nano titanium dioxide comprises the following steps: S11. Add an appropriate amount of nano-titanium dioxide powder to the solvent and treat with ultrasound for 30 min to obtain a dispersed nanoparticle solution; S12. Dissolving a long-chain fatty acid in ethanol, wherein the mass of the long-chain fatty acid is 5% of the mass of the nano-titanium dioxide, to obtain a fatty acid solution; S13. The dispersed nanoparticle solution was transferred to a three-necked flask, and the fatty acid solution was slowly added dropwise, the reaction temperature was controlled at 80° C., and the reaction was stirred for 4 h to obtain a modified nano-titanium dioxide suspension; S14. The modified nano-titanium dioxide suspension is cooled to room temperature, and the modified nano-titanium dioxide is collected by centrifugation, and the product is repeatedly washed with ionized water to remove unreacted stearic acid, and the washed product is vacuum dried at 80°C for 24 hours, and then the dried product is lightly ground and sieved through a sieve to obtain the modified nano-titanium dioxide.

[0030] Example 5 In this embodiment, a heat storage stable polyamide wax powder includes: 100 parts of polyamide wax powder prepared according to the method of Example 1; 5 parts of modified nano titanium dioxide, which is prepared according to Example 3; The modified nano titanium dioxide comprises long-chain fatty acid and nano titanium dioxide.

[0031] The long-chain fatty acid is stearic acid.

[0032] The nano titanium dioxide is anatase type.

[0033] In step S02 of the method for preparing the polyamide wax powder, the combined organic amines include meta-xylylenediamine and diamines with a linear symmetrical structure, wherein the meta-xylylenediamine accounts for 80% of the total amount of the organic amines in the combination, and the diamines with a linear symmetrical structure account for 20% of the total amount of the organic amines in the combination.

[0034] The diamine with a linear symmetrical structure is ethylenediamine.

[0035] In step S11 of the preparation method of modified nano titanium dioxide, the ultrasonic treatment power is 400W, the solvent is anhydrous ethanol, and the mass ratio of the nano titanium dioxide powder to the solvent is 1:10.

[0036] Example 6 In this embodiment, a heat storage stable polyamide wax powder includes: 150 parts of polyamide wax powder prepared according to the method of Example 2; 10 parts of modified nano titanium dioxide, wherein the modified nano titanium dioxide is prepared according to the method of Example 4; The modified nano titanium dioxide comprises long-chain fatty acid and nano titanium dioxide.

[0037] The long-chain fatty acid is oleic acid.

[0038] The nano titanium dioxide is a mixed crystal form.

[0039] In step S02 of the method for preparing the polyamide wax micropowder, the combined organic amines include meta-xylylenediamine and diamines with a linear symmetrical structure, wherein meta-xylylenediamine accounts for 95% of the total amount of the organic amines in the combination, and the diamines with a linear symmetrical structure account for 5% of the total amount of the organic amines in the combination.

[0040] The diamine with a linear symmetrical structure includes a mixture of 1,4-butanediamine, 1,10-decanediamine and p-phenylenediamine in a mass ratio of 1:1:1.

[0041] In step S11 of the preparation method of modified nano titanium dioxide, the ultrasonic treatment power is 500W, the solvent is anhydrous ethanol, and the mass ratio of the nano titanium dioxide powder to the solvent is 1:100.

[0042] Example 7 In this embodiment, a heat storage stable polyamide wax powder includes: 130 parts of polyamide wax powder prepared according to the method of Example 1; 8 parts of modified nano titanium dioxide, which is prepared according to the method of Example 3; The modified nano titanium dioxide comprises long-chain fatty acid and nano titanium dioxide.

[0043] The long-chain fatty acid is palmitic acid.

[0044] The nano titanium dioxide is of plate-like type.

[0045] In step S02 of the method for preparing the polyamide wax micropowder, the combined organic amines include meta-xylylenediamine and diamines with a linear symmetrical structure, wherein the meta-xylylenediamine accounts for 90% of the total amount of the organic amines in the combination, and the diamines with a linear symmetrical structure account for 10% of the total amount of the organic amines in the combination.

[0046] The diamine with a linear symmetrical structure is ethylenediamine.

[0047] In step S11 of the preparation method of modified nano titanium dioxide, the ultrasonic treatment power is 450W, the solvent is anhydrous ethanol, and the mass ratio of the nano titanium dioxide powder to the solvent is 1:50.

[0048] Example 8 In this embodiment, 120 parts of a heat storage stable polyamide wax powder includes: Polyamide wax powder prepared according to the method of Example 2; 7 parts of modified nano titanium dioxide, wherein the modified nano titanium dioxide is prepared according to the method of Example 4; The modified nano titanium dioxide comprises long-chain fatty acid and nano titanium dioxide.

[0049] The long-chain fatty acid is arachidonic acid.

[0050] The nano titanium dioxide is of plate-like type.

[0051] In step S02 of the method for preparing the polyamide wax micropowder, the combined organic amines include meta-xylylenediamine and diamines with a linear symmetrical structure, wherein meta-xylylenediamine accounts for 85% of the total amount of the organic amines in the combination, and the diamines with a linear symmetrical structure account for 15% of the total amount of the organic amines in the combination.

[0052] The diamine with a linear symmetrical structure is 1,3-propylenediamine.

[0053] In step S11 of the preparation method of modified nano titanium dioxide, the ultrasonic treatment power is 450W, the solvent is anhydrous ethanol or isopropanol, and the mass ratio of the nano titanium dioxide powder to the solvent is 1:70.

[0054] Example 9 In this embodiment, the difference from Embodiment 5 is that: The long-chain fatty acid is lauric acid.

[0055] Example 10 In this embodiment, the difference from Embodiment 5 is that: The long-chain fatty acid is lignoceric acid.

[0056] Embodiment 11 In this embodiment, the difference from Embodiment 5 is that: The nano titanium dioxide is rutile type.

[0057] Example 12 In this embodiment, the difference from Embodiment 5 is that: The nano titanium dioxide is of plate-like type.

[0058] Comparative Example 1 In this comparative example, the difference from Example 5 is that: Use VK-T02H nano titanium dioxide to replace modified nano titanium dioxide.

[0059] Comparative Example 2 In this comparative example, the difference from Example 5 is that: No modified nano titanium dioxide is added.

[0060] Comparative Example 3 In this comparative example, the difference from Example 5 is that: Meta-xylylenediamine is used instead of the organic amine of the combination.

[0061] Comparative Example 4 In this comparative example, the difference from Example 5 is that: No modified nano titanium dioxide is added.

[0062] Meta-xylylenediamine is used instead of the organic amine of the combination.

[0063] Test example - sag performance test Add polyamide wax powder to acrylic resin aluminum powder paint, and the addition ratio of polyamide wax powder is 2.5% of the total mass of acrylic resin aluminum powder paint. Use high-speed stirring technology to evenly distribute the polyamide wax in the paint, and raise the temperature of the entire paint system to about 50-60°C. The dispersion process lasts for 30 minutes to obtain modified acrylic resin aluminum powder paint.

[0064] The modified acrylic resin aluminum powder paint was tested according to the National Standard of the People's Republic of China GB / T 9264-2012 "Evaluation of Anti-Sagging Properties of Paints and Varnishes". The testing instrument was a sag applicator, the depth difference between adjacent grooves was 10 μm, the distance between adjacent wet films was 1.5 mm, and the wet film width was 6 mm.

[0065] Glass plates are used for coating panels, and the panels are cleaned according to the provisions of the National Standard of the People's Republic of China GB / T 9271-2008 "Standard Test Panels for Paints and Varnishes".

[0066] The test temperature is 23±2℃ and the relative humidity is 50±5% The polyamide wax rheological agents prepared in some of the above examples and comparative examples were tested, and the results are shown in Table 1. Table 1. Sagging data comparison table Instant sag / μm Heat storage 30d sag / μm Heat storage 60d sag / μm Example 5 550 560 580 Example 6 520 530 550 Example 7 510 510 530 Example 8 520 530 540 Example 9 510 530 550 Example 10 520 530 540 Embodiment 11 510 520 530 Example 12 520 520 530 Comparative Example 1 500 370 330 Comparative Example 2 510 320 290 Comparative Example 3 500 270 220 Comparative Example 4 490 260 200 By comparing the above embodiments and comparative examples, it can be seen that: 1. Comparing Example 5 with Comparative Examples 1 and 2, in Comparative Examples 1 and 2, as the heat storage time increases, the sagging performance decreases significantly, while in Example 5, as the heat storage time increases, the sagging performance increases instead. It can be seen that both nano titanium dioxide and modified nano titanium dioxide can improve the heat storage resistance of the polyamide wax rheological agent and improve its anti-sagging performance, and the improvement effect of modified nano titanium dioxide is more significant; 2. Comparing Example 5 and Comparative Example 3, in Comparative Example 3, as the heat storage time increases, the sagging performance decreases significantly, while in Example 5, as the heat storage time increases, the sagging performance increases instead. It can be seen that the combined organic amine can significantly improve the heat storage resistance of the polyamide wax rheological agent and improve its anti-sagging performance relative to m-phenylenediamine; 3. By comparing Example 5 with Comparative Example 4, it can be seen that the modified nano titanium dioxide and the combined organic amine can more significantly improve the heat storage resistance of the polyamide wax rheological agent and improve its anti-sagging performance; 4. By comparing Example 5 with Examples 9-12, it can be seen that the use of anatase nano-titanium dioxide and the use of stearic acid for modification have better effects on improving the heat storage resistance and anti-sagging performance of the polyamide wax rheological agent.

[0067] The above specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A heat storage stable polyamide wax micropowder, characterized in that: It comprises the following components by weight: 100-150 parts of polyamide wax powder, wherein the raw materials for preparing the polyamide wax powder include a combination of organic amines, and the combination of organic amines includes meta-xylylenediamine and a diamine with a linear symmetrical structure; 5-10 parts of modified nano titanium dioxide, wherein the modified nano titanium dioxide is obtained by surface-modifying the nano titanium dioxide with a long-chain fatty acid.

2. The heat storage stable polyamide wax micropowder according to claim 1, characterized in that: The long-chain fatty acid includes one of lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid and lignoceric acid.

3. The heat storage stable polyamide wax powder according to claim 1, characterized in that: The long-chain fatty acid includes one of oleic acid, linoleic acid, linolenic acid and arachidonic acid.

4. The heat storage stable polyamide wax powder according to claim 1, characterized in that: The nano titanium dioxide includes one of rutile type, anatase type, brookite type and mixed crystal type.

5. A heat storage stable polyamide wax powder according to any one of claims 1 to 4, characterized in that: The preparation method of the polyamide wax micropowder comprises the following steps: S01. A measured amount of an acid is added to the reaction device and the temperature is raised to 100-140°C until the acid is completely melted into a liquid to obtain a product 1; S02. Slowly add the combined organic amine to the product one, the molar ratio of the first type of acid to the organic amine is 2:1, and after the addition is completed, the temperature is raised to 150-160° C. and reacted for a period of time until the acid value drops below 5 to obtain product two; S03. Adding a second type of acid to the product two, the molar ratio of the first type of acid to the second type of acid is (0.85-0.95): (0.05-0.15), and continuing the reaction at a constant temperature until the acid value is less than 5 to obtain a product three; S04. Add the modified nano titanium dioxide to the product three and stir to mix. After mixing, the material can be discharged. After the wax block is completely cooled, it is crushed, coarsely crushed and air flow milled until the particle size of the powder is D98≤15μm, so as to obtain the polyamide wax powder.

6. The heat storage stable polyamide wax micropowder according to claim 5, characterized in that: In step S02, m-xylylenediamine accounts for 80-95% of the total amount of the organic amines in the combination, and the diamines with a linear symmetrical structure account for 5%-20% of the total amount of the organic amines in the combination.

7. The heat storage stable polyamide wax powder according to claim 6, characterized in that: The diamine with a linear symmetrical structure includes a mixture of one or more of ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,10-decanediamine, p-phenylenediamine, and 4,4'-diaminodicyclohexylmethane.

8. A heat storage stable polyamide wax powder according to any one of claims 1 to 4, characterized in that: The preparation method of the modified nano titanium dioxide comprises the following steps: S11. Add an appropriate amount of nano-titanium dioxide powder to the solvent and treat with ultrasound for 20-30 min to obtain a dispersed nanoparticle solution; S12. Dissolving a long-chain fatty acid in ethanol, wherein the mass of the long-chain fatty acid is 1-5% of the mass of the nano-titanium dioxide, to obtain a fatty acid solution; S13. The dispersed nanoparticle solution was transferred to a three-necked flask, and the fatty acid solution was slowly added dropwise, the reaction temperature was controlled between 60-80° C., and the reaction was stirred for 2-4 h to obtain a modified nano-titanium dioxide suspension; S14. Cool the modified nano-titanium dioxide suspension to room temperature, collect the modified nano-titanium dioxide by centrifugation or filtration, repeatedly wash the product with ethanol or deionized water to remove unreacted stearic acid, and vacuum dry the washed product at 60-80°C for 12-24h, then lightly grind the dried product, and sieve it through a sieve to obtain the modified nano-titanium dioxide.

9. The heat storage stable polyamide wax powder according to claim 8, characterized in that: In step S11, the ultrasonic treatment power is 400-500W.

10. The heat storage stable polyamide wax powder according to claim 8, characterized in that: In step S11, the solvent is anhydrous ethanol or isopropanol, and the mass ratio of the nano titanium dioxide powder to the solvent is 1: (10-100).

Citation Information

Patent Citations

  • Preparation method of biodegradable polybutylene succinate

    CN102718950A

  • Method for modifying surface of nano-titanium dioxide powder and application of modified nano-titanium dioxide powder in organic coating

    CN106810911A

  • High-solid-content water-based polyamide wax

    CN114163864A

  • Polyamide resin composition and molded article

    JP2002226705A

  • Powdery polyamide resin composition for thixotropic additive, preparation method thereof, and powdery paints for ship comprising the same

    KR1020120110306A

Cited By

  • Heat storage stable polyamide wax as well as preparation method and application thereof

    CN121379141A

  • Antibacterial high-strength organic composite material and preparation method thereof

    CN121975225A